2018
DOI: 10.1038/s41467-018-05627-1
|View full text |Cite
|
Sign up to set email alerts
|

Apparent bias toward long gene misregulation in MeCP2 syndromes disappears after controlling for baseline variations

Abstract: Recent studies have suggested that genes longer than 100 kb are more likely to be misregulated in neurological diseases associated with synaptic dysfunction, such as autism and Rett syndrome. These length-dependent transcriptional changes are modest in MeCP2-mutant samples, but, given the low sensitivity of high-throughput transcriptome profiling technology, here we re-evaluate the statistical significance of these results. We find that the apparent length-dependent trends previously observed in MeCP2 microarr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 46 publications
(120 reference statements)
3
37
0
Order By: Relevance
“…
10.7554/eLife.38619.027Figure 7—figure supplement 2.Significant length differences using the test proposed by Raman et al (2018) evaluating length dependent differences by comparing expression ratios between groups to those within a single group.( A,B ) (Top panels) Mean and Std. Dev.
…”
Section: Resultsmentioning
confidence: 99%
“…
10.7554/eLife.38619.027Figure 7—figure supplement 2.Significant length differences using the test proposed by Raman et al (2018) evaluating length dependent differences by comparing expression ratios between groups to those within a single group.( A,B ) (Top panels) Mean and Std. Dev.
…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis approaches varied in stringency between experiments, with cut‐off values ranging from p < .05 to .005 and fold change (fc) from >1.2 (<0.67) to >2 (<0.5). These different methodologies are of great consequence to the interpretation of data as subtle changes caused by Mecp2 deficiency may be reported to be important in the less stringent tests which do not reflect the real function of Mecp2 (Raman et al, ). The opposite can also happen, as too few genes may be reported in more stringent tests, hence “loosing” critical data .…”
Section: Analysis Platforms Usedmentioning
confidence: 99%
“…One hypothesis for the pathogenesis of Rett syndrome is that loss-of-function mutations in the MECP2 gene are detrimental because they result in the lack of MeCP2-mediated silencing of transcriptional noise (Bird and Tweedie 1995). It has also been suggested that MeCP2 controls the expression of long genes (more than 100 kb) in a length-dependent manner (Gabel et al 2015), although this view is controversial (Raman et al 2018). Regardless of the specific molecular mechanism(s) of MeCP2 regulation of gene expression (Guy et al 2011), there is ample consensus that MeCP2 is a critical component of the gene structure required for proper transcription.…”
Section: Molecular Mechanisms Of Mecp2 Functionmentioning
confidence: 99%